Dexter : Original sin. Season 1 [videorecording (DVD)]. - Lindsay, Jeffry P. (Showtime Entertainment, 2025)
Miami, 1991. When his bloodthirsty urges can't be ignored any longer, Dexter Morgan must learn to channel his inner darkness as he transitions from student to avenging serial killer. With the guidance of his father, Harry, he adopts a Code designed to help him find and kill people who deserve to be eliminated from society without getting on the radar of law enforcement a particular challenge for young Dexter as he begins a forensics internship at the Miami Metro Police Department.